Numerical Performance Investigation of Hybrid PV/Thermal System - K. Idan Al-Chlaihawi, Kadhim; A. Hamzah, Dhafer; k. Zarzoor, Ahmed; M. Hasan, Yousif (International Journal of Engineering and Technology, 2018)
Promoting reduction of PV temperature plays crucial role in increasing electrical performance. The present work deal with different types of absorber shape for analysing heat transfer phenomena. Serpentine and spiral absorber are using to verify this purpose with different boundary conditions of inlet mass flow rate and inlet temperatures.The recent study was conducted to evaluate the effect of some operating and designing parameters such as solar radiation levels, flow rates, absorber shape and cooling water temperature on the performance of PVT system numerically. Performance of PVT system determined by thermal efficiency, electrical efficiency and the summation of both known as total or PVT efficiency. Solar radiation ranging from 500 W/m2 to1000 W/m2 was introduced and at each, flow rates of water ranging from 0.016 kg/s to 0.05 kg/s. The results show that the performance of PVT increases with a flow rate at all radiation levels. Also the spiral flow absorber gives a higher performance than serpentine absorber where the value of Â of spiral absorber is increased by about 5.2% compared to the value of serpentine absorber, on the other hand, the rate of heat loss (Â decreased by about 10%.Increasing initial cooling water temperature degrades electrical efficiency of PVT system.Â Â